Looking at cultural diversity to interculturalize higher education - Mandepora Chundary, Marcia (Revista Universitaria del Caribe, 2019)
In higher education, interculturality is understood as a synonym for folklore, a synonym for indigenous, and its action is reduced to the functional or romantic sphere. Although, some universities show certain advances from the folklorization of cultures and languages; nevertheless, these initial efforts do not affect curricular transformations, which means that the presence of the diversity of ancestral knowledge and knowings in these academic spaces continues to be disregarded. From indigenous peoples, interculturality clearly denotes its political historical content, that is, it has a highly emancipatory connotation that poses the overcoming of systems of colonial domination and the exercise of their collective and individual rights. This historical and political nature of the interculturality raised by indigenous peoples is not fully understood, which is why the tendencies of folklorizing in the ethnic approach, and in many cases from the pretext that "we are all equal", policies of inclusion and submission are strengthened. From these conceptions it is that this essay reflects on the different ways of understanding interculturality and its implementation, so it is assumed that it is necessary to contribute with elements of discussion to create conditions for progress towards the interculturalization of higher education